Assistance in Strengthening Character to Respect Oneself and Others as a Form of Anti-Bullying in Students of SDN Ngembat Gondang District, Mojokerto Regency - Puguh Satya Hasmara; Ilmul Ma’arif (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
There is something regrettable from SDN Ngembat, which is not in line with the concern of the surrounding residents for the school which is so high, namely that there are still many students of SDN Ngembat who mock each other between friends, laugh when they see their friends embarrassed, even when the service service makes observations at SDN Ngembat there is a student who has the heart to tell other students to climb avocado trees that are high enough to get avocados for him and his classmates. Of course this will be a serious problem in the future if this does not get good handling. It was agreed between the service and the school that a very urgent problem and needed to be handled appropriately was still rampant bullying behavior among students. Community service methods applied in activities are lectures, presentations, modeling, role play, and small group discussions. The result of this service is a decrease in bullying cases that occur, this has been revealed by various sources including, the Principal, Teacher Council, students, even some parents of students said that now their children are more excited to go to school because they feel more comfortable at school than playing in the environment around the house.